Implementation Of Application Based Village Financial System (SISKEUDES) Policy In Minahasa Regency - Claudio G.J. Rantung; Faria Ruhana; Eko Budi Santoso (Sean Institute, 2024)
Implementation of the Application-Based Village Financial System Policy (SISKEUDES) in Minahasa Regency is still not optimal in its implementation. In this research, researchers want to analyze, understand and describe the implementation, obstacles and efforts regarding the Application-Based Village Financial System (SISKEUDES) carried out by the Minahasa Regency Government and the Village Government. This research uses a qualitative approach with descriptive methods. This research uses a qualitative approach with descriptive methods. The sampling technique consists of purposive sampling and snowball sampling. Data collection used by researchers is through observation, interviews and documentation. Data analysis techniques consist of reduction (data reduction), display (data presentation) and verification (drawing conclusions/verification). The results of this research indicate that the implementation of the Application-Based Village Financial System Policy (SISKEUDES) in Minahasa Regency is still not running optimally in terms of implementing E-Government in local government agencies. Obstacles in the Implementation of the Application-Based Village Financial System (SISKEUDES) Policy are: limited number and quality of human resources, conformity with Standard Operating Procedures (SOP). Efforts are being made to overcome obstacles in the Implementation of the Application-Based Village Financial System Policy (SISKEUDES) in Minahasa Regency, namely, increasing the Number and Quality of Human Resources, namely, personnel and equipment as drivers in the village must be managed and empowered effectively and efficiently so that the potential is can be used optimally, then maximize compliance with Standard Operating Procedures (SOP), namely, always coordinating between related parties or village officials and operators. Other efforts can also be made, namely with technical guidance regarding siskeudes which must be carried out routinely every year.